Hazed perceptions: a qualitative analysis of college students' definitions and perceptions of hazing in student organizations - Alexander, Kellie D., author; Opsal, Tara, advisor; Unnithan, N. Prabha, committee member; Donovan, Jody, committee member (Colorado State University. Libraries, 2018)
While hazing gains media coverage when tragedy occurs or incidences of hazing activities are leaked to social media, this topic at universities receives little to moderate sociological attention. Many consider hazing a widespread problem given that some research estimates that as many as 55 percent of college or high school students have been involved in these activities. Notably, however, additional evidence indicates that students often resist understanding hazing activities as such. Clearly, these kinds of attitudes are important to consider when developing anti-hazing programming or campaigns, especially as colleges and universities in the United States have witnessed a steady rise in hazing-related deaths and injuries, which have produced complex legal issues and questions. This study uses data obtained through semi-structured qualitative interviews of college students to understand how members of sororities, fraternities, and sports club teams define and understand hazing. These conceptualizations are compared to their university's official policy around hazing, and the differences and similarities between the two are discussed. This research illuminates three primary themes in how students define hazing, as well as a disjuncture between how students define hazing and how they perceive their own experiences of hazing. Policy implications and broader recommendations around hazing prevention will be considered.
Keywords: hazing; interpersonal violence; college students; student groups; higher education